从《任雨农全集》探知任雨农的教育思想(A Study Of The Educational Thoughts From The “Complete Works Of Ren Yunong”) - Lai, Chui Mun (2018)
This paper focuses on Ren YuNong, the Chinese School Teacher of Malaysia,study about his work and struggle on the Chinese Education, analyses his educational ideal and experiences fighting for Chinese Education, as well as his influence on education and cultural. The author will sort out his life stories, find out the origin of his educational thoughts, and prove that Ren YuNong’s educational thought has Confucian connotation. Chinese calligraphy is developed with the development of Chinese education and other fine arts education. The author will elaborate on this subject, Ren YuNong how to express his humanistic spirit of cultural calligraphy, irrigation it in educational thinking and highlight the role of cultural educators. Then, taking Ren Younong as the research object of this thesis, from Ren YuNong's Collected Books volume one, two and three as the chief source to discover Ren YuNong's educational thoughts. The author will interpret the responsibility of cultural education from Ren YuNong through three categories, which is: Chinese education, issue of promoting Chinese and promote calligraphy. Through this representative case study, the author attempts to study in detail of how Chinese education survive in Malaysia's sensitive ethnic politics, summarizes the causes and experiences of Malaysian Chinese education as a model of overseas Chinese education, and analyzes its development prospects. The author also hopes to promote the study of Malaysian Chinese education at home and abroad. v Finally, summing up the influences of Ren YuNong on Chinese education and his contribution, it is confirmed that heis an important figure in Malaysian’s history, especially his participation in the development of Chinese education in Malaysia.